DIGITAL ECONOMY AND ITS IMPACT ON DEVELOPING COUNTRIES’ PARTICIPATION IN INTERNATIONAL BUSINESS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores the growing influence of the digital economy on the international business participation of developing countries. It highlights how digital technologies—such as e-commerce, digital finance, and online platforms—are transforming traditional business models, reducing barriers to global markets, and creating new opportunities for economic growth.